2020
DOI: 10.21894/jopr.2020.0031
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Dividing Wall Column Model for Fractionation of Oleochemical Fatty Acid

Abstract: Fractionation process of oleochemical products in Malaysia normally uses conventional distillation columns reduced cost and energy consumption. However, research on its feasibility for oleochemical fractionation is Aspen Plus. A step-by-step design procedure was introduced to aid the model development. Economic and environmental assessment was performed and compared with conventional distillation columns. Hydraulic analysis of several packing type was also performed to gain insights on the column hydrodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The NRTL model is the activity coefficient model, typically recommended for mixtures containing nonelectrolyte polar components. Previous reports demonstrated that the NRTL model is suitable for correlating phase behaviors in relevant systems. Although palm oil contains different fatty acids (e.g., myristic, palmitic, oleic, and linoleic acids), we choose tripalmitin as a representative triglyceride to simplify our modeling. As such, each tripalmitin can be hydrolyzed to give three molecules of palmitic acid and one molecule of glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…The NRTL model is the activity coefficient model, typically recommended for mixtures containing nonelectrolyte polar components. Previous reports demonstrated that the NRTL model is suitable for correlating phase behaviors in relevant systems. Although palm oil contains different fatty acids (e.g., myristic, palmitic, oleic, and linoleic acids), we choose tripalmitin as a representative triglyceride to simplify our modeling. As such, each tripalmitin can be hydrolyzed to give three molecules of palmitic acid and one molecule of glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, UNIFAC models cannot be used for FA distillation, as their applicability is limited to temperatures below 425 K 20 . Othman and Rangaiah 26 compare VLE predictions by the standard UNIQUAC and NRTL models, with the ideal gas law to describe the vapor phase, with National Institute of Standards and Technology (NIST) experimental data for lauric and myristic acid, and conclude a best fit is achieved using the NRTL model. However, no analysis was performed on effectiveness of predicting FA VLE for UNIQUAC and NRTL models in combination with the NTH or HOC model.…”
Section: Introductionmentioning
confidence: 99%